High nutrient-density diets for weanling pigs - Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1986)
The increased occurrence of early weaning (4 weeks of age or less) of pigs has resulted in increased problems with a postweaning "lag" in many commercial swine units. The nursery is the weak link of most commercial swine operations. Attention to management factors that affect environment, health, and nutrition is the key to production success with early weaning. During the last decade, major research efforts have been expended by several universities to find nutritional programs to support satisfactory postweaning performance with early-weaned pigs. Ironically, many of the pigs used in these university trials were 4 weeks of age and weighed in excess of 15 lb at weaning. Weaning at 3 weeks of age results in many lightweight pigs (<10>lb) that require increased nutrient density and diet palatability to maintain growth on a dry diet. If these pigs won't consume the diet, or fully utilize the nutrients in the diet, a "lag" in performance or even death can occur. Economic justification of feeding complex diets to 3-week-old weanling pigs must be considered by the individual swine producer. Prior to weaning, the sow provides the pig with about 16, equally spaced, highly digestible meals in a liquid form. This liquid diet contains approximately 30% protein, 35% fat, and 25% lactose on a dry matter basis. After weaning, pigs are normally fed a low fat, low lactose, high carbohydrate diet composed of cereal grain and soybean meal in a dry form. It is not surprising that a 10 lb pig does not immediately establish a social order I find the feeder, adjust to the drastic change in diet, and immediately start eating and gaining weight the first week after weaning. The objective of this paper is to provide justification for a high nutrient-density diet for early-weaned pigs and to give practical application of such a diet.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Weanling pigs; Diets